2015
DOI: 10.1007/s10865-015-9655-0
|View full text |Cite
|
Sign up to set email alerts
|

Attributing discrimination to weight: associations with well-being, self-care, and disease status in patients with type 2 diabetes mellitus

Abstract: This study examined the association between attributing self-reported discrimination to weight and diabetes outcomes (glycemic control, diabetes-related distress, and diabetes self-care). A community dwelling sample of 185 adults (mean age = 55.4; 80% White/Caucasian, 65% female) with poorly controlled Type 2 diabetes (HbA1c level ≥7.5%) provided demographic and several self-report measures (including diabetes-related distress, diabetes self-care activities, discrimination, and attributions of discrimination),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 65 publications
3
43
0
Order By: Relevance
“…In MIDUS, Tsenkova and others [24] noted that experiencing weight discrimination amplified the adverse effects of elevated WHR on HbA1c. Among community-dwelling adults with diabetes, researchers found that participants experienced worse glycemic outcomes if they had experienced weight-based discrimination [11]. Similar to the present study, the changes in glycemic markers persisted even after accounting for body weight and other forms of discrimination [11].…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In MIDUS, Tsenkova and others [24] noted that experiencing weight discrimination amplified the adverse effects of elevated WHR on HbA1c. Among community-dwelling adults with diabetes, researchers found that participants experienced worse glycemic outcomes if they had experienced weight-based discrimination [11]. Similar to the present study, the changes in glycemic markers persisted even after accounting for body weight and other forms of discrimination [11].…”
Section: Discussionsupporting
confidence: 79%
“…By accounting for family relationships within the cohort, we reduced bias related to shared genetic or environmental factors that contribute to weight and metabolic dysregulation. The present study also builds upon existing evidence that self-reported weight discrimination adversely influences biochemical parameters beyond the effect of actual weight [11]. Given the established connection between personal responsibility campaigns and increased obesity stigma [5], the results from this study have important policy implications with respect to framing obesity prevention campaigns as well as treatment implications for clinicians working with clients with obesity.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The stigma associated with both obesity and Type II Diabetes, particularly in childhood and adolescence, are posited to negatively affect the psychological functioning, coping, and positive self-care behaviors in this population [79]. In adults with Type II Diabetes, weight stigma was found to be strongly tied to poor care management such that individuals who strongly felt a weight stigma had poorer self-care behaviors [80].…”
Section: Type II Diabetesmentioning
confidence: 96%